Some approximation properties of a new class of linear operators. Issue 5 (7th August 2019) - Patel, Prashantkumar; Mishra, Vishnu Narayan
Abstract : In the present manuscript, we propose the new modification of Szász‐Mirakyan operators, which is a class of linear positive operators of discrete type depending on two real parameters. We give theorem of degree of approximation, the Voronovskaya asymptotic formula, and statistical convergence. At the end, graphical comparisons and error estimation are shown for these operators.